CBMS-9 INFLUENCE OF HYPOXIA ON PHOTODYNAMIC THERAPY WITH 5-AMINOLEVULINIC ACID FOR MALIGNANT GLIOMA STEM CELLS. (3rd December 2022) - Nonoguchi, Naosuke; Ihata, Tomohiro; Omura, Naoki; Wanibuchi, Masahiko
Abstract: Background: Glioblastoma is a highly malignant brain tumor refractory to standard treatment and its refractoriness is attributed to the presence of a small number of glioma stem cells (GSCs) that survive in a harsh microenvironment. The aim of this study was to investigate the effect of hypoxic conditions on the sensitivity of GSCs to 5-aminolevulinic acid-based photodynamic therapy (ALA-PDT). Materials and Methods: Six human GSClines: three GSCs classified as Mesenchymal subtype and three GSCs classified as Proneural subtype, were divided into normoxia-GSCs (O2: 21%) and hypoxia-GSCs (O2: 5%) groups. To compare the effects of different oxygen partial pressures on protoporphyrin-IX (PpIX) biosynthetic activity, the expression levels of PpIX biosynthetic enzymes and transporters were examined by qRT-PCR and intracellular PpIX concentration was measured by flow cytometry. In addition, the sensitivity of these two cell groups to ALA-PDT was assessed in vitro. Results: Hypoxia-GSCs showed higher mRNA levels of FECH (ferrochelatase), which is required for iron synthesis to convert PpIX to haem, compared to Normoxia-GSCs. Flow cytometry revealed that the accumulation of PpIX from exogenous ALA in Hypoxia-GSCs was reduced compared to in Normoxia-GSCs. Despite this, no Hypoxia-GSC lines showed significantly reduced sensitivity to ALA-PDT compared to Normoxia-GSCs. Conclusion: Hypoxia-GSCs had lower intracellular PpIX accumulation than Normoxia-GSCs due to increased gene expression of FECH, and that their sensitivity to ALA- PDT was reduced less, despite accumulating lower concentrations of PpIX. ALA-PDT is at least a potentially effective therapy for hypoxia-tolerant GSCs that exist in hypoxia at 5% oxygen concentration.